Intravesical adjuvant therapy using mitomycin C - Islam, MA; Bhuiyan, ZH; Shameem, IA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):40-4 The abstract of this article is available on the PubMed website